Anisotropic shape of CsPbBr3 colloidal nanocrystals: from 1D to 2D confinement effects. Issue 36 (11th September 2020) - Steinmetz, Violette; Ramade, Julien; Legrand, Laurent; Barisien, Thierry; Bernardot, Frédérick; Lhuillier, Emmanuel; Bernard, Mathieu; Vabre, Maxime; Saïdi, Imen; Ghribi, Amal; Boujdaria, Kaïs; Testelin, Christophe; et al.
Abstract : Confinement effects on excitonic transitions in CsPbBr3 nanoplatelets and nanosticks are revealed as a function of shapes and thicknesses. Abstract : We synthesized strongly anisotropic CsPbBr3 nanocrystals with very narrow emission and absorption lines associated to confinement effects along one or two dimensions, called respectively nanoplatelets (NPLs) and nanosticks (NSTs). Transmission Electron Microscopy (TEM) images, absorption and photoluminescence (PL) spectra taken at low temperature are very precise tools to determine which kind of confinement has to be considered and to deduce the shape, the size and the thickness of nanocrystals under focus. We show that the energy of the band-edge absorption and PL peaks versus the inverse of the square of the NPL thickness has a linear behaviour from 11 monolayers (MLs) i.e. a thickness of 6.38 nm, until 4 MLs (2.32 nm) showing that self-energy correction compensates the increase of the exciton binding energy in thin NPLs as already observed in Cadmium chalcogenides-based NPLs. We also show that slight changes in the morphology of NSTs leads to a very drastic modification of their absorption spectra. Time-resolved PL of NSTs has a non-monotonous behaviour with temperature. At 5 K, a quasi-single exponential with a lifetime of 80 ps is obtained; at intermediate temperature, the decay is bi-exponential and at 150 K, a quasi-single exponential decay is recovered (≈0.4 ns). For NSTs, the exciton interaction with LO phonons governs the broadening of the absorption and PL peaks at room temperature and is stronger than in chalcogenides quantum dots and NPLs.